How does brand trust enhance satisfaction and loyalty of commercial bank customers? - Krishna C. Alejandrino; Karmela Palma-Samson (Journal of the Academy of Business and Emerging Markets, 2023)
The purpose of the study is to discuss the importance of brand trust in the banking industry in the Philippines. This study aims to determine various factors' effect on customer loyalty in a banking service environment. It empirically tests a model that proposes that consumer brand trust and brand effect influence consumer brand loyalty. We used a partial least squares structural equation modeling (PLS-SEM) to test the hypothesis and model. The findings indicated that customer satisfaction influenced consumer brand loyalty. Additionally, the results have a positive, though nonsignificant, the indirect effect of consumer brand trust on the relationship between satisfaction and consumer loyalty.